Association of diabetes and cigarette smoke exposure on the glycemia and liver glycogen of pregnant Wistar rats - Sinzato, Yuri Karen; Lima, Paula Helena Ortiz; Santos, Carlos Eduardo Meirelles dos [UNESP]; Campos, Kleber Eduardo de [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Damasceno, Débora Cristina [UNESP] (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2008)
Purpose: To evaluate cigarette smoke exposure and/or diabetes association effects on the glycemia and liver glycogen levels of pregnant Wistar rats. Methods: 60 adult rats were randomly distributed into (n= 10/group): non-diabetic exposed to filtered air (G1); non-diabetic exposed to cigarette smoke only before pregnancy (G2); non-diabetic exposed to cigarette smoke before and during pregnancy (G3); diabetic exposed to filtered air (G4); diabetic exposed to cigarette smoke only before pregnancy (G5), and diabetic exposed to cigarette smoke before and during pregnancy (G6). Glycemia was determined at days 0 and 21 of pregnancy. Liver samples were collected for liver glycogen determinations. Results: At day 21 of pregnancy, glycemia was higher in G5 and G6 compared to G4 group. G2 (2.43 +/- 0.43), G3 (3.20 +/- 0.49), G4 (2.62 +/- 0.34), G5 (2.65 +/- 0.27) and G6 groups (1.94 +/- 0.35) presented decreased liver glycogen concentrations compared to G1 (4.20 +/- 0.18 mg/100mg liver tissue) (p<0.05). G5 and G6 groups presented decreased maternal weight gain and litter weight. Conclusions: Severe diabetes and cigarette smoke exposure, alone or associated, caused impairment in liver glycogen storage at term pregnancy. Due to the fact that liver glycogen storages were considered determinant for glucose tolerance, it is relevant to point out a rigid clinical glycemic control and to stop smoking so earlier in pregnancy programming.

OBJETIVO: Avaliar a associação da exposição à fumaça de cigarro e/ou diabete sobre a glicemia e concentrações de glicogênio hepático em ratas Wistar prenhes. MÉTODOS: 60 ratas adultas foram distribuídas aleatoriamente em seis grupos (n=10/grupo): não-diabético exposto ao ar filtrado (G1); não-diabético exposto à fumaça de cigarro antes da prenhez (G2); não-diabético exposto à fumaça de cigarro antes e durante a prenhez (G3); diabético exposto ao ar filtrado (G4); diabético exposto à fumaça de cigarro antes da prenhez (G5); diabético exposto à fumaça de cigarro antes e durante a prenhez (G6). A glicemia foi determinada nos dias 0 e 21 de prenhez. Foram coletadas amostras de fígado para dosagens de glicogênio. RESULTADOS: No 21º dia de prenhez, a glicemia foi maior nos grupos G5 e G6 comparados ao grupo G4. Os grupos G2 (2,43±0,43), G3 (3,20±0,49), G4 (2,62±0,34), G5 (2,65±0,27) e G6 (1,94±0,35) apresentaram concentrações de glicogênio diminuídas comparados ao grupo G1 (4,20±0,18 mg/100mg) (p <0.05). Os grupos G5 e G6 apresentaram ganho de peso materno e peso da ninhada diminuídos. CONCLUSÕES: O diabete grave e a exposição à fumaça de cigarro, sozinhos ou associados, causaram prejuízo no armazenamento de glicogênio na prenhez a termo. Devido ao fato dos estoques de glicogênio serem determinantes para a tolerância à glicose, é imprescindível indicar um rígido controle glicêmico e deixar de fumar antes da gestação.
Associação entre diabetes e exposição à fumaça de cigarro sobre a glicemia e glicogênio hepático de ratas Wistar prenhes
Keywords: Diabetes Mellitus, Experimental; Pregnancy; Glycogen; Tobacco Smoke Pollution; Glycemia; Rats